Dietary Diversity among Tanzanian Women: Insights from National Panel Survey Wave 4 Data - SWAI, Aleswa; MSOGA, Japhet; JOHN KAMUHABWA, Jocelyn; MUKASA, Oscar (African Journal of Nutrition and Dietetics, 2025)
Tanzania’s national surveys offer potential for calculating Minimum Dietary Diversity for Women (MDD-W), a key health indicator. However, apart from the 2022 Tanzania Demographic and Health Survey (TDHS), most surveys lack the necessary data variables for MDD-W trend analysis, leaving national trends unreported for nearly two decades. This study used National Panel Survey Wave 4 (NPS4) data to estimate a proxy MDD-W value for 2014/2015, comparing it with TDHS 2022 findings. The 2014 data was selected due to its 8-year interval, a reasonable timeframe to assess changes. Sixty food items were categorized into 10 groups (FAO, 2021), focusing on women aged 15–49. Data were linked using unique identifiers to household food consumption records. Grains, roots, and tubers were consumed by 56.62%, while only 19.3% ate meat, poultry, or fish. Other food groups had under 3% consumption. Slightly more than half (57%) of women consumed at least two food groups, and only 8% consumed 5 or more food groups. This analysis reveals alarmingly low and stagnant dietary diversity among Tanzanian women of reproductive age. With a consistent MDD-W of 8% from 2014/15 to 2022, progress has stalled. Diets remain overly dependent on staples and lack vital, nutrient-rich foods.